Innate activation of human primary epithelial cells broadens the host response to Mycobacterium tuberculosis in the airways. - Ann-Kathrin Reuschl; Michael R Edwards; Robert Parker; David W Connell; Long Hoang; Alice Halliday; Hannah Jarvis; Nazneen Siddiqui; Corrina Wright; Samuel Bremang; Sandra M Newton; Peter Beverley; et al. (PLoS Pathogens)
Early events in the human airways determining whether exposure to Mycobacterium tuberculosis (Mtb) results in acquisition of infection are poorly understood. Epithelial cells are the dominant cell type in the lungs, but little is known about their role in tuberculosis. We hypothesised that human primary airway epithelial cells are part of the first line of defense against Mtb-infection and contribute to the protective host response in the human respiratory tract. We modelled these early airway-interactions with human primary bronchial epithelial cells (PBECs) and alveolar macrophages. By combining in vitro infection and transwell co-culture models with a global transcriptomic approach, we identified PBECs to be inert to direct Mtb-infection, yet to be potent responders within an Mtb-activated immune network, mediated by IL1β and type I interferon (IFN). Activation of PBECs by Mtb-infected alveolar macrophages and monocytes increased expression of known and novel antimycobacterial peptides, defensins and S100-family members and epithelial-myeloid interactions further shaped the immunological environment during Mtb-infection by promoting neutrophil influx. This is the first in depth analysis of the primary epithelial response to infection and offers new insights into their emerging role in tuberculosis through complementing and amplifying responses to Mtb.